Raising Dairy Herd Replacements - Dhuyvetter, Kevin C.; Smith, John F.; Harner III, Joseph P.; Brouk, Micheal (My University, 2002)
This publiction discusses the decision making factors for raising dairy herd replacements.
MF399_2002_10
Keywords: MF399; Economics; Livestock; MF